150k views
5 votes
5. Sara thinks the following expressions are equivalent:

2x + 3 = x/2 + 3/4
Is she right? If so, prove that these two expressions are equivalent. If not, what error(s) did she make?​

1 Answer

4 votes


\sf\purple{No, \:Sara\: is \:wrong.}


2x + 3≠ (x)/(2) + (3)/(4)


\sf\red{Here's\:why:}


L. H. S. = 2x + 3


R. H. S = (x)/(2) + (3)/(4) \\ = (x * 2)/(2 * 2) + ( 3)/(4) \\ = (2x + 3)/(4)

Clearly,


2x + 3≠ (2x + 3)/(4) \\✒ \: L.H.S.\:≠\:R. H. S.


\boxed{Therefore,\:the\:two\:expressions \:are\:not\:equivalent.}

To make them equivalent, Sara can simply divide L. H. S. by 4.

By doing so, she'll have


(2x + 3)/(4) = (2x + 3)/(4) \\ ๛L.H.S.=R. H. S


\large\mathfrak{{\pmb{\underline{\orange{Happy\:learning }}{\orange{!}}}}}

User Mara Black
by
6.0k points